The World on Screen: The Internet as a Communication Media for Deaf People - Date Suwangsa Juan Arun; Candrasari, Yuli (HM Publisher, 2024)
Deaf people face various challenges in communicating, especially in a wider social context. The Internet has emerged as a potential communication tool to overcome these barriers. This research aims to understand in depth how deaf people use the internet as a communication medium and how this affects their lives. This research uses a qualitative approach with a case study design. Data was collected through in-depth interviews with 15 deaf people who were members of the community at SLB Kemala Bhayangkari 2 Gresik. Thematic analysis was used to identify key themes from the data obtained. The research results show that the internet has a significant role in the lives of deaf people. The Internet is used for a variety of communication purposes, including communicating with friends and family, accessing information, participating in online communities, and expressing oneself. In addition, the internet also helps deaf people develop social skills, increase self-confidence, and reduce feelings of isolation. The Internet has opened up new opportunities for deaf people to communicate and participate in society. These findings have important implications for educators, policy makers, and technology developers in designing and providing inclusive internet access for deaf people.